New Indices from Polysomnographic Measures for the Severity of Obstructive Sleep Apnea Syndrome -A Different Look at Obstructive Sleep Apnea Syndrome - (:unkn) unknown (TURKISH NEUROPSYCHIATRY ASSOC-TURK NOROPSIKIYATRI DERNEGI, 2018)
Introduction: Obstructive sleep apnea syndrome (OSAS) is characterized by recurrent abnormal respiratory events during sleep and causes oxidative stress which is reported as a major pathogenic mechanism for the development of various cardiovascular disorders. For the diagnosis and management of treatment, disease-related symptoms and the Apnea-Hypopnea Index (AHI) measured from polysomnographic (PSG) recordings are taken together. However, AHI do not sufficiently represent the total hypoxic load, and other indices related to apnea frequency, apnea duration, and desaturation degree should be investigated. Methods: In this study, 317 polysomnographic recordings were retrospectively evaluated. Apart from the conventional AHI, apnea and/or hypopnea duration percentage (AHDP) and desaturation area (DesatArea) were calculated using PSG data. Results: According to the AHI, 21.8%, 32.8% and 45.4% of cases were grouped as mild, moderate and severe OSAS, respectively. When AHDP was taken into account, 10.4%, 22.1% and 67.5% of the cases were regrouped as mild, moderate or severe OSAS, respectively. When the DesatArea calculation was used, the grouping of cases as mild, moderate or severe OSAS changed in value to 10.7%, 21.1% and 68.1%, respectively. The total group change was found to be 58.4% for both the AHDP and DesatArea formulation. With the AHDP formulation, regrouping was made in 52.2% of the mild OSAS cases and 62.5% of the moderate OSAS cases; by using the DesatArea calculation, 50.7% of mild OSAS cases and 63% of moderate OSAS cases were regrouped. Conclusion: Our results show that when another parameters related to abnormal respiratory events are used, the same patients within the same group of disease severity are heterogeneously separated according to severity of hypoxia. It is suggested that grouping the patients based on AHI is insufficient and that using other polysomnographic measurements along with AHI should be considered to represent the severity of the disease.
Keywords: desaturation; apnea duration; obstructive sleep apnea; severity; OXIDATIVE STRESS; INTERMITTENT HYPOXIA; PARAMETERS; EVENTS